SOSIALISASI DAN PELATIHAN PRAKTIS MENGHITUNG PAJAK BAGI UMKM MELALUI DJP ONLINE - Elmawati, Nissa; Aprilina, Vita; Fakhran Al Ramadhan, Muhammad (Universitas Islam 45 Bekasi, 2024)
Micro, Small, and Medium Enterprises (MSME) constitute a pivotal component of the Indonesian economy. Nevertheless, the majority of MSME in Wibawamulya Village continue to encounter difficulties in comprehending the procedures for obtaining a Taxpayer Identification Number (NPWP), calculating and paying taxes in an appropriate manner. This results in the potential for tax revenue from the MSME sector to be underestimated. In order to address these issues, a programme entitled 'Socialisation and Training on Tax Calculation for MSME through DJP Online' was implemented, comprising three stages: community education, training, and evaluation. The objective of this programme is twofold: firstly, to educate MSME on their tax obligations; and secondly, to train them in the calculation and payment of taxes in accordance with the DJP Online system. It is anticipated that the programme will have a beneficial impact on the economy of Wibawamulya Village, particularly in terms of enhancing MSME tax compliance and augmenting tax revenue from this sector